Comparison of time and method in freeze-marking cattle - Schalles, R.R.; Drake, C.L.; Allen, Dell M. (Kansas State University. Agricultural Experiment Station, 2011)
Freeze marking for within-herd identification was used on 65 Hereford females. The cattle were 18 months to nearly three years old. Three numerals were placed on the right rump of each animal in the fall of 1967. The “branding irons” used were four-inch brass numerals with a half inch face. Dry ice and ethyl alcohol were used as the coolant with 40, 50 and or 60 seconds of contact time as well as liquid nitrogen with 39, 35 or 40 seconds of contact. Three men each applied one of the three numerals using dry ice and alcohol coolant with 60 seconds contact time on 14 head. The remaining 51 head were marked by one man.
Keywords: Beef; Freeze marking; Dry ice; Ethyl alcohol